2020
DOI: 10.1371/journal.pone.0236619
|View full text |Cite
|
Sign up to set email alerts
|

Enacting national social distancing policies corresponds with dramatic reduction in COVID19 infection rates

Abstract: The outbreak the SARS-CoV-2 (CoV-2) virus has resulted in over 6.5 million cases of COVID19, greatly stressing global healthcare infrastructure. Lacking medical prophylactic measures to combat disease spread, many nations have adopted social distancing policies in order to mitigate transmission of CoV-2. While mathematical models have suggested the efficacy of social distancing to curb the spread of CoV-2, there is a lack of systematic studies to quantify the real-world efficacy of these approaches. Here, we f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 11 publications
(15 reference statements)
5
113
0
Order By: Relevance
“…In the spotlight are government interventions [11] the preparedness of the healthcare system [12], risk factors [13], economic [14], political [15] and social factors. Among social factors, the one that received the most attention in the context of COVID-19 is the phenomenon of social distancing [16,17]. Several other authors have focused on social trust [8], social behaviour [18] and the well-being of individuals [19].…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spotlight are government interventions [11] the preparedness of the healthcare system [12], risk factors [13], economic [14], political [15] and social factors. Among social factors, the one that received the most attention in the context of COVID-19 is the phenomenon of social distancing [16,17]. Several other authors have focused on social trust [8], social behaviour [18] and the well-being of individuals [19].…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…Studies conducted in China [47,48] and the United States [49] have provided early evidence that social distancing can successfully reduce infection transmission. Reduction of mobility is at the heart of social distancing [17]. It is important that the decision to stay at home is not only the result of an imposed government restriction, but also reflects the selfimposed COVID-19 strategies of avoiding individuals [16,50,51].…”
Section: Dimensions Of the Reaction Process-government Interventionsmentioning
confidence: 99%
“…The South Korean government implemented protective measures against the spread of COVID-19, including a national infectious disease plan stemming from the 2015 MERS outbreak; nationwide contact tracing efforts; and a ban on the export of face masks [ 4 , 5 ]. Such policies that encourage protective behaviors such as social distancing have been found to be effective in reducing the spread of COVID-19 [ 6 ]. Many of these social distancing measures, such as school closures and the subsequent transition to online learning, greatly affect adolescents, and researchers have found that the continued spread of COVID-19 has many deleterious effects on adolescents’ mental, physical, and socioemotional health [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is no certain treatment for COVID-19 and most of the available treatments are provided to control the symptoms [3]. Currently, it seems that the best and most effective way to reduce the number of infected cases, as well as the number of COVID-19 related death, is to follow official infection control measures and practice social distancing [2,4].…”
Section: Introductionmentioning
confidence: 99%